Mesenchymal Stromal Cells Derived Extracellular Vesicles Ameliorate Acute Renal Ischemia Reperfusion Injury by Inhibition of Mitochondrial Fission through miR-30 - Di Gu; Xiangyu Zou; Guanqun Ju; Guangyuan Zhang; Erdun Bao; Yingjian Zhu (Stem Cells International)
Background. The immoderation of mitochondrial fission is one of the main contributors in ischemia reperfusion injury (IRI) and mesenchymal stromal cells (MSCs) derived extracellular vesicles have been regarded as a potential therapy method. Here, we hypothesized that extracellular vesicles (EVs) derived from human Wharton Jelly mesenchymal stromal cells (hWJMSCs) ameliorate acute renal IRI by inhibiting mitochondrial fission through miR-30b/c/d. Methods. EVs isolated from the condition medium of MCS were injected intravenously in rats immediately after monolateral nephrectomy and renal pedicle occlusion for 45 minutes. Animals were sacrificed at 24 h after reperfusion and samples were collected. MitoTracker Red staining was used to see the morphology of the mitochondria. The expression of DRP1 was measured by western blot. miR-30 in EVs and rat tubular epithelial cells was assessed by qRT-PCR. Apoptosis pathway was identified by immunostaining. Results. We found that the expression of miR-30 in injured kidney tissues was declined and mitochondrial dynamics turned to fission. But they were both restored in EVs group in parallel with reduced cell apoptosis. What is more, when the miR-30 antagomirs were used to reduce the miRNA levels, all the related effects of EVs reduced remarkably. Conclusion. A single administration of hWJMSC-EVs could protect the kidney from IRI by inhibition of mitochondrial fission via miR-30.